HUBUNGAN ANTARA FAKTOR PERSONAL DAN FAKTOR SOSIAL DENGAN PELAKSANAAN INISIASI MENYUSUI DINI DI RUMAH SAKIT UMUM DAERAH DR. A. DADI TJOKRODIPO KOTA BANDAR LAMPUNG - Rilyani Rilyani; Vivi Yolanda (Universitas Malahayati Lampung, 2019)
ABSTRACT: RELATIONSHIP BETWEEN PERSONAL FACTORS AND SOCIAL FACTORS WITH THE IMPLEMENTATION OF INITIATED BREASTFEEDING IN DR. A. DADI TJOKRODIPO REGIONAL PUBLIC HOSPITAL BANDAR LAMPUNG CITY Introduction: Early initiation of breastfeeding in the first 30 minutes of birth is one of the ten steps to successful breastfeeding. Breastfeeding rates in the first hour after birth were highest in East and South Africa (65%) and lowest in East Asia and the Pacific (32%). In Indonesia, the 2016 IMD was 51.9%. in Lampung province at 24.1%, in Bandar Lampung City it was only 18.6% and in DR AUD Hospital Dadi Tjokrodipo still did not apply the IMD compared to other hospitalsObjective: It is known the relationship between personal factors and social factors with the implementation of early breastfeeding initiation at the Regional General Hospital DR A Dadi Tjokrodipo, Bandar Lampung City in 2019.Method: The type of research used in this study is quantitative research. Research design with cross sectional approach. The population in this study were all maternity mothers with a sample of 48 taken by purposive sampling. There are two variables in this study, Independent variables: knowledge, motivation, attitude, husband's support, the role of the officer. The dependent variable in this study is Early Breastfeeding Initiation. Data analysis is univariate (frequency distribution) and bivariate using the chi square test.Results: It is known that respondents did not succeed in implementing IMD, as many as 31 (75.6%) respondents. Respondents with bad knowledge were 26 (63.4%), most respondents with negative attitudes as many as 25 (61.0%) respondents, most of the respondents with negative motivation were 30 (73.2%) respondents. Respondents with negative husband support as many as 24 (58.5%) respondents and most of the respondents with no psychic disorders revealed negative officer roles as many as 25 (61.0%). There is a relationship between knowledge and implementation of breastfeeding initiation (p-value 0.002; OR 13.714), attitude (p-value 0.007; OR 11,500), motivation (p-value 0.001; OR 15,750), role (p-value = 0.007; OR 11, 50), husband's support (p-value 0,008; OR 9,778). Suggestions of health workers should be able to further increase the motivation of mothers to implement IMD through approaches to mothers and husbands so that they can help implement the IMD in infants. Keywords: Early Initiation Of Breastfeeding, Personal Factors, Social Factors INTISARI: HUBUNGAN ANTARA FAKTOR PERSONAL DAN FAKTOR SOSIAL DENGAN PELAKSANAAN INISIASI MENYUSUI DINI DI RUMAH SAKIT UMUM DAERAH DR. A. DADI TJOKRODIPO KOTA BANDAR LAMPUNG Pendahuluan: Inisiasi menyusi dini dalam 30 menit pertama kelahiran merupakan salah satu dari sepuluh langkah menuju keberhasilan menyusui. Tingkat menyusui dalam satu jam pertama setelah kelahiran tertinggi di Afrika Timur dan Selatan (65%) dan terendah di Asia Timur dan Pasifik (32%). Di Indonesia yang mendapat IMD tahun 2016 sebesar 51,9%. di provinsi Lampung sebesar 24,1%, di Kota Bandar Lampung hanya sebesar 18,6 % dan di RSUD DR A Dadi Tjokrodipo masih belum menerapkan IMD jika dibandingkan dengan rumah sakit lainTujuan : diketahui hubungan antara faktor personal dan faktor sosial dengan pelaksanaan inisiasi menyusui dini di Rumah Sakit Umum Daerah DR A Dadi Tjokrodipo Kota Bandar Lampung Tahun 2019.Metode : Jenis penelitian kuantitatif, rancangan penelitian dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh ibu bersalin dengan sampel sebanyak 48 yang diambil secara purposive sampling. Variabel dalam penelitian ini ada dua yaitu: Variabel independen: pengetahuan, Motivasi, sikap, dukungan suami, peran petugas. Variabel dependen dalam penelitian ini adalah Inisiasi Menyusu Dini. Analisa data secara univariat (distribusi frekuensi) dan bivariat menggunakan uji chi square.Hasil Penelitian : Diketahui responden tidak berhasil melaksanakan IMD, yaitu sebanyak 31 (75,6%) responden. Responden dengan pengetahuan tidak baik yaitu 26 (63,4%), sebagian besar responden dengan sikap negatif yaitu sebanyak 25 (61,0%) responden, sebagian besar responden dengan motivasi negatif sebanyak 30 (73,2%) responden. Responden dengan dukungan suami negatif sebanyak 24 (58,5%) responden dan sebagian besar responden dengan tidak ada gangguan psikis mengungkapkan peran petugas negatif yaitu sebanyak 25 (61,0%). Ada hubungan pengetahuan dengan pelaksanaan inisiasi menyusui (p-value 0,002 ; OR 13,714), sikap (p-value 0,007 ; OR 11,500), motivasi (p-value 0,001 ; OR 15,750), peran (p-value = 0,007 ; OR 11,50), dukungan suami (p-value 0,008 ; OR 9,778). Saran petugas kesehatan hendaknya dapat lebih meningkatkan motivasi ibu untuk melaksanakan IMD melalui pendekatan kepada ibu dan suami sehingga dapat membantu terlaksananya pelaksanaan IMD pada bayi. Kata kunci: IMD, Faktor Personal, Faktor Sosial